2019
DOI: 10.1002/advs.201802001
|View full text |Cite
|
Sign up to set email alerts
|

A Multifunctional Biodegradable Nanocomposite for Cancer Theranostics

Abstract: Theranostic formulations, integrating both diagnostic and therapeutic functions into a single platform, hold great potential for precision medicines. In this work, a biodegradable theranostic based on hollow mesoporous organosilica nanoparticles (HMONs) is reported and explored for ultrasound/photoacoustic dual‐modality imaging guided chemo‐photothermal therapy of cancer. The HMONs prepared are endowed with glutathione‐responsive biodegradation behavior by incorporating disulfide bonds into their framework. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 51 publications
0
65
0
Order By: Relevance
“… 14 , 20 These attractive features indicate that ICG could be a promising dye for tumor imaging and PTT. 11 , 21 So far, ICG has been used for the determination of liver function and liver blood flow, 22 cardiac output, 23 and ophthalmic angiography. 24 Nevertheless, several intrinsic drawbacks limit its ideal application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“… 14 , 20 These attractive features indicate that ICG could be a promising dye for tumor imaging and PTT. 11 , 21 So far, ICG has been used for the determination of liver function and liver blood flow, 22 cardiac output, 23 and ophthalmic angiography. 24 Nevertheless, several intrinsic drawbacks limit its ideal application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…45,46 These may provide solutions to the potential risk of uncontrolled degradation of the silica framework and unwanted in vivo retention. 47 It has been demonstrated that Se@SiO 2 NPs increased the resistance of airway epithelium to LPS-induced oxidative injury and improved outcomes of ALI mice. In fact, several nanodevices have been reported to protect against this disorder through different ways.…”
Section: Discussionmentioning
confidence: 99%
“…These materials exhibited higher proton mobility in mesopore channels and can be degraded entirely in 24 h in simulated body fluid [ 188 ]. MSN degradation can also be accelerated by the inclusion of biodegradable [ 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 ] or water-soluble components [ 199 ]. To minimize premature release, pores can be blocked by gatekeepers.…”
Section: Nanocarrier Platforms and Binding Strategiesmentioning
confidence: 99%
“…Disulfide bonds can be incorporated in multiple locations to enhance responsiveness. For example, in Wu et al’s work, both a disulfide-bridged precursor and a disulfide-linked gatekeeper, PTX prodrug, were used in an MSN-based DDS [ 197 ]. The photothermal agent indocyanine green (ICG) and ultrasound imaging agent, perfluoropentane (PFP), were encapsulated as cargo in the system.…”
Section: Stimulimentioning
confidence: 99%